Temporal Experience, Temporal Passage and the Cognitive Sciences. Issue 8 (August 2015) - Baron, Samuel; Cusbert, John; Farr, Matt; Kon, Maria; Miller, Kristie
Abstract Cognitive science has recently made some startling discoveries about temporal experience, and these discoveries have been drafted into philosophical service. We survey recent appeals to cognitive science in the philosophical debate over whether time objectively passes. Since this research is currently in its infancy, we identify some directions for future research.